2021
DOI: 10.1002/jmv.27484
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of rotavirus strains circulating in Norway before and after the introduction of rotavirus vaccination in children

Abstract: Globally, rotavirus (RV) is the leading cause of acute gastroenteritis (AGE) in young children under 5 years of age. Implementation of RV vaccination is expected to result in fewer cases of RV in the target population, but it is unknown if this also results in vaccine‐induced virus strain replacement. Rotarix, a monovalent vaccine based on G1P[8] RV, was introduced in Norway in the children's immunization program in September 2014. The main aim of this study was to describe the diversity of RV circulating pre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…The introduction of RV vaccination has succeeded in nearly halving the number of global RV deaths from 453,000 in 2008 to 215,000 in 2013 (Moyo et al, 2014; Tate et al, 2012). Indeed, RV vaccines continue to be successful in minimizing disease severity as well as hospitalizations and thus reducing mortality from RV infection, but the infection nevertheless remains ineradicable, showing multiple outbreaks and greater diversity of circulating RV genotypes in the post-vaccination period documented in our previous studies (Hoque et al, 2020 ; Okitsu et al, 2022 ) as well as by other groups (Gibory et al, 2022 ; Gikonyo et al, 2020 ; Tsugawa et al, 2021 ). A similar diversity of RV genotypes was observed in the present study at SW (Table 1 ).…”
Section: Discussionmentioning
confidence: 61%
“…The introduction of RV vaccination has succeeded in nearly halving the number of global RV deaths from 453,000 in 2008 to 215,000 in 2013 (Moyo et al, 2014; Tate et al, 2012). Indeed, RV vaccines continue to be successful in minimizing disease severity as well as hospitalizations and thus reducing mortality from RV infection, but the infection nevertheless remains ineradicable, showing multiple outbreaks and greater diversity of circulating RV genotypes in the post-vaccination period documented in our previous studies (Hoque et al, 2020 ; Okitsu et al, 2022 ) as well as by other groups (Gibory et al, 2022 ; Gikonyo et al, 2020 ; Tsugawa et al, 2021 ). A similar diversity of RV genotypes was observed in the present study at SW (Table 1 ).…”
Section: Discussionmentioning
confidence: 61%
“…Despite substantial efforts in rotavirus vaccination and the presence of high vaccination rates among rotavirus‐positive children, it remains the most prevalent virus in our study, often in combination with norovirus. The distribution of rotavirus types shows significant variation between different countries, hinting at strain replacement and a potential vaccine escape phenomenon 17 . Nevertheless, further studies on the genetic diversity of circulating viruses are needed to explore this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of rotavirus types shows significant variation between different countries, hinting at strain replacement and a potential vaccine escape phenomenon. 17 Nevertheless, further studies on the genetic diversity of circulating viruses are needed to explore this aspect.…”
Section: Comparison Between Children With Dual-virus Detection and Ea...mentioning
confidence: 99%
“…These findings align with a recent study in Norway, where G1P[8] was the most common genotype in similar age groups. 31 However, a study in India reported a higher prevalence of G1P[8] in children under 36 months and a lower infection with G9P[4] genotype in older children. 32 The tendency of specific RVA genotypes in certain age groups could be attributed to differences in host factors and the virus genotypes in different populations.…”
Section: Discussionmentioning
confidence: 99%